Keterampilan Metakognitif Siswa Climber dalam Pemecahan Masalah Matematika - Febryanto Kurniawan; Puji Nugraheni; Wharyanti Ika Purwaningsih; Teguh Wibowo (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
This research aims to describe metacognitive skills of climber students in solving mathematic problems in class VIII junior high school. The subject of research isthree climber students of Junior High School 3 Purworejo. The research method used qualitative with the form of phenomenological research. The subject of research is climber students of Junior High School 3 Purworejo. The research instrument is an Adversity Quotient questionnaire, mathematic troubleshooting test, and interviews. Data collection techniques are conducted by collecting data from writing test and interview with students. The results showed that climber students planning skills at the stage of understanding problems and planning problem solving is aware in predicting the knowledge of materials needed and have the thoroughness in digging information that is important in the matter, aware of the plan used and able to realize the relationship with the problems that ever worked. Climber students monitoring skills on the stage of implementing a solving plan, students are aware in the process of solving questions and aware that previous strategies can assist in solving the problem, students also aware and confident with the results of his work. Mean while, climber students evaluation skills realize that the results are correct, but students not realize that there are other strategies that can solve the problem.